Evaluation of the drinking water treatment system (STAP) San Fernando –Los Patios urbanization, Colombia. Efficiency and quality (2020)
The quality of water for human consumption in the municipality of Los Patios in Colombia, depends 60% of the treatment systems for drinking water (STAP) independent, these are adapted according to the population that conforms in 2014 and own resources. Urbanization San Fernando carries out the treatment in an efficient way guaranteeing the quality of water for human consumption, therefore, the field study is based on a quantitative approach and a method that describes the results of the analysis of the samples taken at the entrance and exit of the STAP, to evaluate the efficiency and quality of the system the sample is characterized from the analysis of the physical-chemical and microbiological parameters at the entrance and exit of the system in the Water Laboratory of the Universidad Francisco de Paula de Santander. The physical and microbiological results identify the efficiency of the system and the operator, indicating the quality of the water by the values in the parameters measured according to Decree 1575 of 2007 and 1525 of 2007 by the Ministry of Social Protection in Colombia. The chemical analyses detected a high percentage of calcium hardness in the sample at the system outlet, which is reportedto the directors of the urbanization. In accordance with this, the relevant controls and monitoring are carried out in the process for the purification and consumption of water, without neglecting the habits of water storage by the community in each home.